An Analog Template-Based Classifier Using MOS Translinear Loops. (8th June 2011) - Farshidi, Ebrahim
Abstract : An analog template matching pattern classifier circuit based on a new synthesis of Euclidean distance calculation is presented. It is composed of simple two-quadrant squarer/divider blocks. The circuit employs MOSFETs that operate in strong inverted saturation region performing electronically simulated translinear loop. The converter features very low supply voltage (0.9 V), immune from body effect, two-quadrant input current, large dynamic range, and low circuit complexity. The circuit was successfully applied to the recognition of some simple patterns. Simulation results by HSPICE show high performance in the separation of circuit and confirm the validity of the proposed technique.